Tragedy's endurance : performances of Greek tragedies and cultural identity in Germany since 1800 - Fischer-Lichte, Erika (Classical presences, 2017)
This volume explores performances of Greek tragedies in Germany since 1800 as responses to particular political, social and cultural milestones, shedding light on how, in a constantly changing political and cultural climate, they influenced the evolving cultural identity of the educated middle class over that period